Cumulative Incidence of Osteochondritis Dissecans of the Capitellum in Child and Adolescent Baseball Players - Iwame, Toshiyuki (Orthop J Sports Med, 2016)
OBJECTIVES: Prevalence of osteochondritis dissecans (OCD) of the capitellum is high among individuals who have played baseball since childhood. Recently two cross-sectional studies according to prevalence of OCD have been published. In a study of 1040 baseball players aged 10 to 12 years, Matsuura et al found that 2.1% of players had OCD, with no differences in prevalence according to age or player position. Kida et al., in their study of 2433 baseball players aged 12 to 18 years, found OCD in 3.4% of subjects. Furthermore, they found that players with OCD began playing baseball at earlier ages, had played for longer periods, and had experienced more elbow pain. The player’s current baseball position may not be related to the existence of OCD lesions. Together, these findings led us to examine the longitudinal study for examining the risk factors for occurrence of OCD. Our objectives were to determine (1) cumulative incidence rates of OCD in the school child players aged 6-11 years old, (2) the relative risk of OCD by age, beginning age playing baseball, playing period, experimental hours per week, playing position, and elbow pain. METHODS: A total of 1,275 players aged 6-11 years (mean, 9.4 years) belonged to youth baseball teams without OCD lesions received examination in the next year and were the subjects of this investigation. Subjects were examined by questionnaire, and ultrasonographic and radiographic examination. Questionnaire items included age, player position, beginning age of playing baseball, playing period of baseball, number of training hours per week and history of elbow pain. Ultrasonography of the lateral aspect of the elbow was performed. An irregularity of the subchondral bone of the capitellum was regarded as an abnormality. Radiographic examination was recommended to players who had an abnormal finding on ultrasonographic examination. We investigated the following risk factors for occurrence of OCD: age, player position, beginning age of playing baseball, playing period of baseball, number of training hours per week, and history of elbow pain. Data were analyzed by multivariate logistic regression models and presented as odds ratio (OR) and profile likelihood 95% confidence interval (CI) values. RESULTS: The mean age that players were introduced to baseball was 6.6 ±1.1 years; the mean duration of play baseball was 2.7 ±1.1 years; and the proportion of players with elbow pain when throwing was 24.1%. There were 138 (10.8%) pitchers, 114 (8.9%) catchers, 524 (41.2%) infielders, and 499 (39.1%) outfielders. The initial ultrasonographic screening revealed an irregularity of the subchondral bone in 33 players (2.6%). Of the 33 players, all the players agreed to undergo radiography. Of them, 23 players were confirmed OCD. These results showed that cumulative incidence of OCD was 1.8%. Univariate analysis showed that OCD occurrence was significantly associated with age of 11-12 years (p<.01) and more than 3 years of experimental year (p<.01). Beginning age of playing baseball, number of training hours per week, playing position, and history of elbow pain were not significantly associated with OCD. Multivariate analysis showed that age of 11-12 years (OR, 3.96; 95% CI, 1.10-18.97) was risk factors significantly associated with OCD. Experimental year was not significantly associated with OCD occurrence. CONCLUSION: It is expected that 1.8% of youth baseball players have OCD each year. The age of 11 and 12, increased training hours per week are risk factors for OCD.